Material Incentives for Innovation and Rationalization in Soviet Enterprises during 1960s to 1980s - D. A. Pinaeva; E. R. Salakhutdinova (Научный диалог)
This article addresses the issues of funding innovative activities in the USSR during the second half of the 20th century. It argues that an effective mechanism for material incentives for innovation was never established in the Soviet Union. The study demonstrates that the resources allocated for the development of invention and rationalization were used ineffectively by both ministries and agencies, as well as by public organizations. In the context of a planned economy, achieving an optimal balance of interests among stakeholders in the process of creating and utilizing inventions was virtually unattainable. Through specific examples and statistical data, it is shown that innovators gradually shifted their efforts from developing and implementing major inventions and rationalization proposals to minor improvements that could be easily adopted by enterprises, reflected in statistical reports, and for which they received modest but stable rewards. It was found that payments intended to expedite the creation and dissemination of innovations became arbitrary disbursements to managerial staff and administrative employees, who often had no direct involvement with the innovations produced. The conclusion drawn is that the funding mechanism for innovative activity in the USSR did not foster a sustainable motivation for effective inventive and rationalization efforts.